2020
DOI: 10.1021/acsomega.0c02130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Diamond Crystallization in Metal–Carbon Systems

Abstract: In this article, we report the influence of oxygen concentration in the transition-metal solvent-catalyst on the crystallization processes, morphology, and defect-and-impurity content of diamond crystals. In a series of experiments, the concentration of oxygen ( C O ) in the growth system was varied by adding Fe 2 O 3 to the charge, and the other parameters and conditions of the growth were constant: Ni 7 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Regarding the first observation, a possible explanation might be found in the process of diamond crystallization in metal-carbon systems. Palyanov et al recently reported that oxygen can greatly affect the crystallization ( Palyanov et al, 2020 ). They found that the concentration of O 2 higher than 0.25 wt% can lead to spontaneous nucleation events which hinders crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the first observation, a possible explanation might be found in the process of diamond crystallization in metal-carbon systems. Palyanov et al recently reported that oxygen can greatly affect the crystallization ( Palyanov et al, 2020 ). They found that the concentration of O 2 higher than 0.25 wt% can lead to spontaneous nucleation events which hinders crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Hasil EDAX tersebut memperlihatkan perbandingan persentase komposisi kimia material pembentuk, yaitu unsur In=18,29% dan unsur Se=81,71% atau 2 : 9 padahal perbandingan bahan yang diinginkan adalah 2 : 3. Hal ini dimungkinkan karena adanya unsur lain yang muncul pada saat preparasi seperti unsur O. Selain itu pada saat proses pengelasan untuk membentuk kapsul kemungkinan oksigen masih dapat masuk ke dalam tabung sangat besar, sebab pada proses pengelasan ini meskipun telah dilakukan dengan sangat hati-hati, sangat sulit dilakukan dan memerlukan waktu yang lama sehingga pada daerah pengelasan (tabung pyrex) dapat terjadi lubang yang berukuran kecil (pori), melalui pori tersebut udara dari luar terutama bahan untuk mengelas (oksigen) dapat masuk dengan mudah, karena pada saat pengelasan tabung masih dalam kondisi divakum dengan tingkat kevakuman yang tinggi [17].…”
Section: Analisis Komposisi Kimia Ingot Atau Massif In2se3unclassified
“…Existing ideas about the polygenic origin of diamonds in nature (see reviews [3,4,26]) involve various processes, mechanisms, and driving forces for diamond crystallization in nature [3,4,26,40,50,51]. According to classical models [3,4,15], in the lithospheric mantle diamond formation occurs at depths of 120-210 km and temperatures of 900-1500 • C as a result of metasomatic processes.…”
Section: Natural Processes and Mechanisms Of Diamond Formationmentioning
confidence: 99%